Perancangan dan Implementasi Aplikasi Peminjaman Ruangan Kedinasan Kota Salatiga menggunakan Framework Laravel - Timothy Wijaya; Ramos Somya (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The lobby loaning was an activity normally carried out in government agencies, especially in the city of salatiga. Room loans were usually made by visiting the service where they intended to borrow a room and meeting the person in charge of the room borrowing. But it was not uncommon for government officials to have difficulty lending, both from borrowers and from lending services. In this respect, salatiga city bygone has not applied information technology principles specific to the loan room. Causing as many problems as time flies, data search is difficult because room loan accounts are still being done by hand. In this study, a formal introduction to room loan requests can make registration, loan archive material, and accessibility of loan-related information easier. There's room for the salatiga city office. Designing the application using SDLC methodology (system development lifecycle), this stage begins with demand analysis, design, application, testing, and maintenance. The application has the function of sending room loan reminders by email so that the borrower can figure out the loan schedules that have been made.